ANALISIS KEDUDUKAN KEUANGAN NEGARA DALAM BUMN YANG TELAH DIPRIVATISASI - WAFDANSYAH ANGGI HUSAINI; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
The problem related to the privatization of State–Owned Corporations is as an urgent issue recently. It is as the effect of nationality assets as the target of privatization which is frequently debated as the existence of the policy to sell some state owned corporations for the foreigners. In other words, the problem occurs in the privatization of State Owned Corporations as the impact of government policy without considering the needs of the people in general. The problem to raise in this thesis is related to rule governing the privatization of State Owned Corporations, legal aspects of state financial in privatization of State Owned Corporations, and the state financial condition in State Owned Corporations which have been privatized. The method used in this research was normative yuridical. Normative research method was also called as doctrinal research, that is the research to analyze law either law as it is written in the book or law it is decided by the judge through judicial process. Normative law research was based on secondary data and emphasized on the steps of speculative-theoretical and normative-quantitative analysis. The privatization program is intended to increase the performance and valued-added of the company as well as to add the participation of the people in the possession of company shares. The privatization was done by paying attention on the principles of transparencies, self-support, accountability, responsibility, and reasonably. The privatization can be done by selling shares based on capital market clauses, share direct selling for investors, and share selling for management and/or related employees. State financial in State Owned Corporations is as different wealthy from the wealthy of state and with the rights to get profit from the results of the company. The wealthy of the state in one State Owned Corporation depends on the type of the corporations. If the type of State Owned Corporations are in Public Company, then all capital shall be owned to state. However, if it is in the form of limited company, then partly of the capital (at least 51%) shall be as the asset of state and it is divided on the shares. State Owned Corporations which have been privatized in fact shall transfer partly of state shares (represented by government) on the state financial in State Owned Corporations which have been privatized to private parties and the possession of shares will be smaller than 50%. It means that new investors as the holder of shares in State Owned Corporations which have been privatized may get partly of shares in State Owned Corporations. As the biggest shareholders, new investors shall try hard and efficiently to get optimal profit, absorb new workers and give more contribution for the government through tax payment and dividend division. Key words : State Financial, State Owned Corporation, Privatization